PENGARUH KUALITAS PELAYANAN, KEPUASAN, DAN KEPERCAYAAN TERHADAP LOYALITAS KONSUMEN PT SUMBER ALFARIA TRIJAYA, TBK - Devirman, Bayu; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2021)
At this time the competition in the retail business world is getting tougher with the increasing number of shopping centers. The retail business is a business that continues to experience development and is in great demand. Competition makes companies in the retail sector strive to become the retail choice for consumers and to retain their consumers. This study aims to determine the effect of service quality, satisfaction, and trust on consumer loyalty at PT Sumber Alfaria Trijaya, Tbk. The method used is quantitative with the design of causality using multiple linear regression analysis. The sample used in this study were 135 consumers of PT Sumber Alfaria Trijaya, Tbk. The data were processed using the SPSS version 23 program. Simultaneously service quality, satisfaction, and trust have a positive effect with F count 101.260 > 2.67 F table and a significant 0.000 < 0.05 on consumer loyalty PT Sumber Alfaria Trijaya, Tbk. The results of the determination test state that service quality, satisfaction, and trust have a correlation with consumer loyalty by 69.2%, while the remaining 30.8% is influenced by other variables not examined in this study.